Expression Profiling and Cellular Localization of Stress Responsive Proteins in Squamous Cell Carcinoma of Human Esophagus. (2nd July 2016) - Iqbal, Mir Khurshid; Zargar, Mohammad Afzal; Mudassar, Syed; Lone, Ghulam Nabi; Yaseen, Syed Besina; Andrabi, Khurshid Iqbal
ABSTRACT: Background : The ambiguity in relating expression dynamics of stress response proteins with human esophageal squamous cell carcinoma (ESCC) has sidelined the potential of stress proteins as therapeutic targets. This study was an attempt to unequivocally relate the stress protein dynamics with stage and propensity of ESCC. Methods : Surgically resected tumor and adjacent histologically normal tissue from 46 patients with esophageal squamous cell carcinoma were investigated in the present study. Expression of HSPs was analyzed by Western blotting and immunohistochemistry. Results : HSP expression was observed in all 46 cases both in adjacent normal and tumor tissues. The expression and the localization of individual HSP showed no significant correlation with depth of invasion, tumor grade, and pathological stage of the tumor. HSP 27 was the most abundant protein followed by HSP 90 and HSP 70. The HSP 27 localized exclusively in the cytoplasm of adjacent normal and tumor cells. HSP 70 showed dispersed expression with predominating nuclear localization in both normal and tumor tissue cells and HSP 90 was localized in cytoplasm of adjacent normal and in nucleus of tumor cells in majority of the cases. Conclusion : Our data advocate lack of relationship between stress protein expression and the progression of ESCC. The data renew the prospect of anti-HSP drugs as therapeutic resources in light of the possibility that their use would continue to sensitize cancer cells towards drug induced apoptosis for tumor regression.